2014
DOI: 10.5152/ucd.2014.2154
|View full text |Cite
|
Sign up to set email alerts
|

Is three-gland-or-less parathyroidectomy a clinical failure for secondary hyperparathyroidism?

Abstract: Objective: To compare the clinical and biochemical outcomes between adequate and inadequate parathyroidectomies in patients with chronic renal failure. Material and Methods:All secondary hyperparathyroidism patients who were previously operated in the Marmara University Hospital Breast and Endocrine Surgery Unit were planned to be included in the study. Patients were divided into two groups according to their extent of surgery: "adequate" and "inadequate" surgery groups. "Adequate surgery" was regarded as eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In support of the latter, a significantly lower failure rate has been associated with adequate in comparison to inadequate surgery (defined as more vs less than 3½ gland resection). 31 Secondly, some studies have demonstrated lack of correlation between percent IOPTH decline and operation outcome or postoperative PTH in renal HPT patients, findings which question the efficiency of IPM in assuring the adequacy of renal HPT surgery. 32,33 However, in addressing these two issues, it has been demonstrated that both neck sides could possibly be explored through the central access provided by video-assisted neck surgery (VANS).…”
mentioning
confidence: 99%
“…In support of the latter, a significantly lower failure rate has been associated with adequate in comparison to inadequate surgery (defined as more vs less than 3½ gland resection). 31 Secondly, some studies have demonstrated lack of correlation between percent IOPTH decline and operation outcome or postoperative PTH in renal HPT patients, findings which question the efficiency of IPM in assuring the adequacy of renal HPT surgery. 32,33 However, in addressing these two issues, it has been demonstrated that both neck sides could possibly be explored through the central access provided by video-assisted neck surgery (VANS).…”
mentioning
confidence: 99%